Malaria in Mice: Models to the Discovery of Novel Anti-Malaria Drugs in Humans - ภัทรดิลกรัตน์ สิทธิพร (KKU Science Journal, 2013)
Malaria parasites are prevalent in a wide range of vertebrate hosts, including rodents. Rodent malaria parasites have been adapted to complete its life cycle in laboratory mice (Mus musculus) and Anopheles mosquitoes, and they can therefore be used as a model to study host-parasite interaction, immunology and chemotherapy that are intractable to study using the human malaria parasites. In this review, the life cycle and the applications of malaria parasites in laboratory mice as a research tool for discovery of new anti-malaria drugs are described.